The role of phase angle and standardized phase angle in assessing nutritional status and predicting complications in gastrointestinal cancer - Dan Zhang; Jiajia Wang; Song Liang; Ping Zhu; Hao Guo; Xinghao Ma (PLoS ONE, 2026)
Objective This study aims to look at the link between bioelectrical impedance analysis (BIA), especially phase angle (PA) and standardized phase angle (SPA), and how often postoperative infectious complications occur in patients with gastrointestinal tumors. Material and methods We chose 139 patients who had gastrointestinal tumor surgery. We did BIA tests on them, assessed their nutritional status with the Patient-Generated Subjective Global Assessment (PG-SGA) scale, checked body composition indicators, and tested their blood markers. The patients were categorized into high PA and low PA groups based on their PA values, and the differences in nutritional status-related indicators and infection rates between these groups were analyzed. Additionally, PA values were standardized, resulting in the formation of high SPA and low SPA groups, and further comparisons of nutritional indicators and infection rates between these groups were conducted. Results Our results show that PA and SPA are very important for checking the nutritional status of patients with digestive tract cancer. They are also closely linked to the chance of having postoperative complications. The study encompassed an analysis of 139 patients with digestive tract cancer, leading to several key conclusions: Firstly, a strong correlation was observed between PA and nutritional status, with malnourished patients demonstrating significantly lower PA values compared to those with adequate nutritional status. Secondly, the group with low PA was significantly associated with several adverse indicators, including advanced age, a higher proportion of females, increased prevalence of chronic diseases, lower BMI, elevated PG-SGA scores, higher incidence of sarcopenia, and reduced skeletal muscle mass and skeletal muscle index. Thirdly, patients categorized in the low SPA group exhibited a significantly higher incidence of complications relative to those in the high SPA group. Lastly, high SPA was significantly associated with a lower incidence of postoperative infectious complications, whereas TNM staging was significantly associated with a higher incidence of these complications. Conclusion This study substantiates the utility of PA and SPA in evaluating the nutritional status of patients with digestive tract cancer and in being associated with postoperative complications. PA demonstrates a significant correlation with malnutrition, sarcopenia, and various body composition indicators, while SPA is significantly associated with postoperative infectious complications.